To Assess the Knowledge and Determinants Associated with Blood Donor at National Medical College & Teaching Hospital, Birgunj (Med Phoenix, 2023)
Introduction: In clinical practice, the two most crucial systems of blood grouping are ABO and Rh. There exist four primary blood types, namely A, B, AB and O. World Health Organization advocates for the compulsory screening of all blood donations prior to usage, with HIV, hepatitis B and C, as well as syphilis being mandatory. The aim of the study is to assess the knowledge and determinants associated with blood donors at National Medical College & Teaching Hospital, Birgunj.Materials and Methods: Proposal was reviewed by the Institutional Review Committee of National Medical College and approved on 9th July 2023. (Ref. F-NMC/662/079-080). A descriptive cross-sectional study was done in the blood donation programs organized in the premises of National Medical College. Sampling method used was census.Results: Of the total particiants, 41.3 % were overweight followed by 39.1 % who showed the normal weight and 7.6 % of the people were found to be underweight. The upper middle-class group accounted for 71.7 % of the total respondents, knowledge about how frequently a person can donate the blood were in 38(41.31%), the volume of blood collected in one pint at the time of donation was 33(35.86%), time taken nearly 5-8 minutes were 64 (69.56%). Among the donors 17(18.47%) had donated for first time in their life similarly for second time and more than three times were 38(41.31%), 38(41.31%), 26(28.26%) and 11(11.95%), respectively.Conclusion: The overall level of knowledge was satisfactory. Male participants had more practice regarding blood donation rather than females. Community shall be benefited by similar set up as made by health workers, blood bank and hospital.